Benefits and challenges of utilizing Chat-GPT and Gamma.app in teaching, learning and assessment of vocational students in 21st century colleges of education in Enugu State - Onuoha I. Okocha; Ebube I. Aneke; Olaiya Adekunle; Ogochukwu Egbuchulam; Anthony Uwanjimgba (The Proceedings of the Nigerian Academy of Science)
The study aimed at assessing the benefits and challenges of utilizing ChatGPT (Generative Pre-trained Transformer) and Gamma.app during teaching, learning and assessment of vocational students at 21st Century Colleges of Education in Enugu State. The study used descriptive survey research design, was guided by three research questions and had a population of 120 respondents; comprising 60 vocational educators and 60 vocational education students who were selected from 3 Colleges of Education. A 3-sectioned questionnaire comprising closed-ended itemized questions with a four-point Likert-type rating scale was developed and used to elicit the opinions of the respondents on each item statement. Data collected were analyzed using mean and standard deviations. The findings of the study show that both vocational educators and vocational students were of same opinion (no significant difference in opinions) on utilizing ChatGPT and Gamma.app during teaching, learning and assessment such as preparing lecture contents and doing assignments. Both groups’ responses having an average mean score above 2.50 is a clear indication that ChatGPT and Gamma.app should be utilized during teaching, learning and assessment. The study highlighted 16 benefits of utilizing ChatGPT and Gamma.app in teaching, learning and assessment of 21st century vocational education students. The study also highlighted 12 challenges militating against utilization of ChatGPT and Gamma.app to include; lack of internet network infrastructure, lack of technical support, lack of training and support of lecturers, challenges with cheating during online assessment, limited time to complete course content, high level societal digital illiteracy, mass poverty among citizens, the absence or total lack of electricity and poor planning.